Perlindungan Hukum terhadap Korban Pelecehan Seksual Pada Anak dibawah Umur - Rika Andriyanti; Sumriyah Sumriyah (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
Legal protection for victims of sexual abuse of minors is very important to guarantee children's rights and provide justice for them. Sexual abuse of children is an act of violence that can have serious impacts on the psychological, social, and physical development of children. Therefore, the state, through various legal policies, plays a role in protecting children from the threat of sexual abuse. In Indonesia, various regulations have been set to provide protection, such as the Child Protection Law, which regulates children's rights to protection from sexual violence. In addition, clear legal mechanisms and psychological assistance processes are also very necessary to ensure the recovery of victims after the incident. The importance of a child-friendly justice system is also highlighted in legal protection efforts, considering that victims often feel intimidated and marginalized in the legal process. A court process that is sensitive to the psychological condition of children will help reduce further trauma for victims. Legal protection also includes imposing strict sanctions on perpetrators to provide a deterrent effect, as well as educating the public about the importance of protecting children from sexual abuse. The government and related institutions must work together to strengthen this protection system.